2012
DOI: 10.1016/j.jaad.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-report photosensitivity in cutaneous lupus erythematosus

Abstract: Background Little is known about the prevalence of self-reported photosensitivity and its effects on quality of life in a U.S. cutaneous lupus population Objective We sought to determine the prevalence of self-reported photosensitivity among a cutaneous lupus population and to examine its impact on quality of life Methods 169 subjects with lupus were interviewed about photosensitivity symptoms and completed the modified Skindex-29+3, a quality of life survey. A complete skin exam was conducted and the Cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 49 publications
2
51
0
1
Order By: Relevance
“…Compared to other reports, incidence of systemic involvement in SCLE patients was higher in the study group. 11,14,15 Similar observations in ACLE and CCLE were made by others. 7,10,16 LE-nonspecific skin lesions were seen exclusively in patients with SLE.…”
Section: Discussionsupporting
confidence: 81%
“…Compared to other reports, incidence of systemic involvement in SCLE patients was higher in the study group. 11,14,15 Similar observations in ACLE and CCLE were made by others. 7,10,16 LE-nonspecific skin lesions were seen exclusively in patients with SLE.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, it has been suggested that patient history of photosensitivity does not necessarily correlate with photoprovocation results. The data on patient history of photosensitivity vary greatly in studies published in the literature (4,25,26), but a recent well-designed study on the prevalence of self-reported photosensitivity in a US population observed that 68% of the CLE patients reported prior or ongoing photosensitivity (27). Our present analysis revealed that 56.9% of CLE patients had a positive history of unusual reactions to sunlight.…”
Section: Discussionmentioning
confidence: 56%
“…85, 86 Rates vary depending on the type of lupus. 87, {Kim, 2013 #9253} 88 Wavelengths within the UVA and/or UVB are responsible for production of cutaneous lesions.…”
Section: Photoimmunological Diseasesmentioning
confidence: 99%